Control interno y cumplimiento de mestas en la empresa regional de servicio público de electricidad del Oriente S.A. Iquitos año 2022 - Molina Gallardo, Gina (2022)
The study shows the general objective: to determine the relationship between internal control and the fulfillment of goals of the employees of the Empresa Regional de Service Public de Electrician del Orient S.A Iquitos year 2022. Being a descriptive - correlational research and non-experimental design, taking 152 collaborators as a sample, the survey was applied as a technique through the questionnaire instrument to obtain information in the study. Concluding that the internal control variable has been qualified as regular (26%) because that company sometimes has a code of ethics; furthermore, it rarely clearly specifies the objectives for risk identification; where there are rarely adequate security controls for access to documents and files. In the same way, the fulfillment of goals was qualified as regular by 26%, due to the fact that it regularly complied in promoting sustainable development, and guaranteeing the quality of the electricity supply, but it did not fully comply in incorporating good corporate management practices, without However, if it complied in achieving a work environment that promotes work productivity. Determining that there is a significant relationship between internal control and achievement of goals, corroborated by a significant positive coefficient and significance of (r=0.795; p=0.000).